Occurrence of commonly used pesticides in personal air samples and their associated health risk among paddy farmers in Tanjung Karang, Malaysia - Mohamad Hamsan, Hazwanee (2017)
Introduction: Tanjung Karang, Selangor is widely known for its paddy cultivation activity and hosts the third largest paddy field in Malaysia. Pesticides contamination in agriculture fields has become an unavoidable problem and farmers are the major group of workers who are constantly handling pesticides. The occupational exposure to pesticides via inhalation could results in both acute and chronic health effects. Objective: This study aims to quantify the concentration of the commonly used pesticides (azoxystrobin, buprofezin, chlorantraniliprole, difenoconazole, fipronil, imidacloprid, isoprothiolane, pretilachlor, propiconazole, pymetrozine, tebuconazole, tricyclazole and trifloxystrobin) in personal air samples, assess their potential health risk to paddy farmers, determine the correlations between climatological conditions (wind speed and temperature) and the concentration of pesticides in personal air samples, determine the association between the proper usage of personal protective equipment (PPE) and self reported respiratory health symptoms among paddy farmers and determine the relationship between self reported respiratory health symptoms and pesticides exposure among paddy farmers. Methodology: A cross-sectional study was carried out at Tanjung Karang, Selangor and eighty-three farmers were involved in this study. A solid sorbent tube was attached to the farmer’s breathing zone with a clip, and an air pump was fastened to the belt to collect personal air samples. Pesticides collected in the XAD-2 resin were extracted with acetone, centrifuged, concentrated via nitrogen blowdown and reconstituted with 1 mL of 3:1 ultrapure water:High-performance liquid chromatography (HPLC)-grade methanol solution. The extract was analyzed using ultra-high performance liquid chromatography tandem mass spectrometry (UHPLCMS/ MS). The health risk of pesticides due to inhalation exposure was calculated for non-carcinogenic (hazard quotients (HQ) and hazard index (HI)) and carcinogenic (lifetime cancer risk (LCR)) health risk. Result: The target compounds were detected with a maximum concentration reaching up to 462.50 ng m-3 (fipronil) and pretilachlor had the highest mean concentration (107.19 ng m-3). The HQ was less than 1 for all the target compounds and the HI value was 3.86 × 10-3, indicating that the risk of pesticides related diseases was not significant. The LCR for pymetrozine was at an acceptable level (LCR<10-6) with 4.10 × 10-8. The self-reported respiratory health symptoms by the paddy farmers reported in this study are as follows: breathing difficulty (16.9%), chest pain (15.7%), cough (41.0%), phlegm (39.8%), and wheezing (18.1%). Spearman’s correlation coefficient test stated that the concentrations of chlorantraniliprole, fipronil and pymetrozine were affected by windspeed and temperature. Simple logistic regressions analysis indicated that exposure to azoxystrobin, buprofezin, chlorantraniliprole, fipronil, isoprothiolane, pretilachlor, propiconazole, tricyclazole and trifloxystrobin were contributing factors that affect selfreported respiratory health symptoms in this study. Conclusion: There were no significant non-carcinogenic and carcinogenic health risks among farmers in the study area. The results reported in this study can be beneficial in terms of risk management within the agricultural community and contributed to the knowledge of pesticides exposure to farmers working on paddy fields in Malaysia.